Hand Hygiene Education and Manufacture of Hand Sanitizer in Miftahul Khoeriyah Madrasah, Bungursari District - Amalia, Siska; Syfa, Syfa; Handayani, Hani (AbdimasMu UMTAS, 2024)
Covid-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). For the first time this virus was discovered in Wuhan, China at the end of December 2019. Because this virus spreads very quickly through droplets released by infected humans, WHO (World Health Organizer) then announced that this disease had become an emergency, requiring infected countries to impose a lock down system to slow the spread of the virus. The Covid-19 virus was first identified in Indonesia in March 2020 and the government imposed activity restrictions and made recommendations for a Health Protocol that must be adhered to to date to prevent its spread. One of the health protocols that must be obeyed is washing hands properly in 6 steps. Hand washing can be done with soap and clean running water, or by using a hand sanitizer. Using a hand sanitizer is easy and practical because you can take it anywhere and it doesn't take a long time, but its availability is limited and the price is quite expensive. Therefore, we want to teach the children and teaching staff at Miftahul Khoeriyah how to make hand sanitizers independently with the basic ingredients of aloe vera, alcohol and essential oil. This activity was carried out on September 5 2021 located at the Miftahul Khoeriyah Madrasah, Bungursari District